Serious Mental Illness in Nursing Homes: Roles and Perceived Competence of Social Services Directors. Issue 7 (3rd October 2021) - Gammonley, Denise; Wang, Xiaochuan; Simons, Kelsey; Smith, Kevin M.; Bern-Klug, Mercedes
ABSTRACT: Providing nursing home psychosocial care to persons with serious mental illnesses (SMI) requires understanding of comorbidities and attention to resident rights, needs and preferences. This quantitative study reports how 924 social service directors (SSDs) taking part in the National Nursing Home Social Service Director survey identified their roles and competence, stratified by the percentage of residents with SMI. More than 70% of SSDs, across all categories of homes, reported the social services department was "always" involved in conducting depression screening, biopsychosocial assessments and PASRR planning. SSDs in homes with lower concentrations of residents with SMI reported less involvement in anxiety screening. Those employed in homes with higher concentrations of residents with SMI reported lower involvement conducting staff interventions for resident aggression or making referrals. More than one-fifth of SSDs lacked confidence in their ability to compare/contrast dementia, depression, and delirium or to develop care plans for residents with SMI. SSDs' perceived competence in developing care plans for residents with SMI was associated with education and involvement in care planning. About one-quarter of social services directors reported not being prepared to train a colleague on how to develop care plans for residents with SMI. Training in SMI could enhance psychosocial care.